A metal organic framework material, a solid phase microextraction probe and a preparation method and application thereof
Patent Information
- Application Number
- CN202311279707.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-09-28
- Publication Date
- 2026-10-16
- Estimated Expiration
- 2043-09-28
AI Technical Summary
[0004]针对现有固相微萃取技术不能很好地适用于检测呼出气中痕量VOCs的问题,本发明提供一种金属有机框架材料、固相微萃取探针及其制备方法和应用
[0021] S1, etch and clean the end of the metal wire to obtain a pretreated metal wire;
Smart Images

Figure CN117186435B_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of organic-inorganic composite materials technology, and in particular to a metal-organic framework material, a solid-phase microextraction probe, its preparation method and application. Background Technology
[0002] Biomarkers are biochemical indicators used to objectively measure and evaluate physiological or pathological conditions. Volatile organic compounds (VOCs) in human exhaled breath are one type of biomarker. They are produced during physiological or metabolic processes and can be released directly into exhaled breath or participate in blood circulation, being released into exhaled breath through the alveoli and lung membranes. Scientific research has found that differences in VOC concentrations in exhaled breath are related to abnormal health conditions in the human body. If a malignant tumor develops, its pathophysiology causes metabolic changes, and tumor cells will produce unique VOCs reflecting the disease condition, leading to changes in the composition and concentration of VOCs. Therefore, by detecting the concentration of cancer-characteristic VOCs in the exhaled breath of different populations, early cancer screening and diagnosis can be achieved. Exhaled breath detection technology has advantages such as being non-invasive and allowing for rapid and convenient sample collection. However, exhaled breath is complex in composition, and the VOC content is relatively low (generally at the ppt to ppb level). Therefore, a simple, rapid, and efficient technique for enriching VOCs is needed before analyzing and detecting them in exhaled breath.
[0003] Solid-phase microextraction (SPME) is an environmentally friendly sample pretreatment technique with advantages such as minimizing matrix influence, selective enrichment of target analytes, no need for large amounts of organic solvents, easy coupling with other analytical instruments, and automation. It has gained widespread attention in the field of analytical detection in recent years. Currently, research in SPME mainly focuses on the preparation of fiber coatings with high enrichment efficiency and high selectivity. However, existing extraction coating materials cannot effectively enrich trace amounts of VOCs in exhaled breath. Therefore, developing an adsorbent material that can efficiently enrich VOCs in exhaled breath is key to overcoming the bottleneck problem of detecting VOCs in exhaled breath using current solid-phase microextraction techniques. Summary of the Invention
[0004] To address the problem that existing solid-phase microextraction (SPE) techniques are not well-suited for detecting trace VOCs in exhaled breath, this invention provides a metal-organic framework material, a SPE probe, its preparation method, and its application.
[0005] To solve the above-mentioned technical problems, in a first aspect, the technical solution provided by the present invention is:
[0006] A metal-organic framework material, wherein the molecular formula of the metal-organic framework material is: [Fe(2,6-NDC)(DMF)] x], where 2,6-NDC is 2,6-naphthalenedicarboxylic acid, DMF is N,N-dimethylformamide, Fe is ferric ion, and 1.2≤x≤1.3.
[0007] In the above technical solution, a metal-organic framework (MOF) material was synthesized by coordinating ferric ions with 2,6-naphthalenedicarboxylic acid ligands. This MOF material has abundant iron-coordinated unsaturated metal sites as Lewis acid centers, exhibiting a strong affinity for aldehydes containing oxygen atoms, thus effectively adsorbing and enriching aldehydes. Simultaneously, using 2,6-naphthalenedicarboxylic acid as the organic ligand, with its two benzene rings, increases the hydrophobicity of the MOF material, effectively preventing water molecules from occupying adsorption sites, thereby improving the enrichment factor. Furthermore, the 2,6-naphthalenedicarboxylic acid molecule has two 180° oriented carboxyl functional groups, which help form a rigid framework structure with numerous functional adsorption sites on its surface. The MOF material formed using this organic ligand exhibits excellent adsorption and enrichment performance of VOCs in exhaled air, and its stable structure makes it suitable for various analytical instruments, showing broad application prospects.
[0008] Secondly, the present invention provides a method for preparing the metal-organic framework material, comprising the following steps:
[0009] Soluble ferric salt, 2,6-naphthalenedicarboxylic acid, and N,N-dimethylformamide were mixed evenly, heated, and reacted in a hydrothermal reactor. After solid-liquid separation, washing, and drying, a metal-organic framework material was obtained.
[0010] This preparation method is simple to operate, has low product preparation cost, and can be mass-produced industrially.
[0011] Preferably, the soluble trivalent iron salt is ferric chloride.
[0012] Preferably, the reaction temperature is 120℃~200℃ and the reaction time is 10h~24h.
[0013] Preferably, the molar ratio of the soluble ferric salt to 2,6-naphthalenedicarboxylic acid is 0.8 to 1.2:1.
[0014] Preferably, the molar ratio of N,N-dimethylformamide to the soluble trivalent iron salt is 360–410:1.
[0015] Optimal reaction conditions and reactant ratios promote a complete reaction, allowing Fe to... 3+ It is fully coordinated with 2,6-naphthalenedicarboxylic acid.
[0016] Thirdly, the present invention provides the application of the metal-organic framework material as an adsorbent in a solid-phase microextraction probe.
[0017] The metal-organic framework material provided by this invention can be used to prepare solid-phase microextraction probes. The metal-organic framework material provided by this invention is adhered to a metal wire by an adhesive, and after curing, a solid-phase microextraction probe with high selectivity and adsorption capacity for VOCs in exhaled air can be obtained.
[0018] Fourthly, the present invention provides a solid-phase microextraction probe, comprising a metal wire, an extraction layer, and a metal protective syringe for protecting the extraction layer; wherein the extraction layer comprises the aforementioned metal-organic framework material.
[0019] In one specific embodiment of the present invention, stainless steel wire with a diameter of 0.3 mm is selected as the metal wire.
[0020] Fifthly, the present invention provides a method for preparing a solid-phase microextraction probe, comprising the following steps:
[0021] S1, etch and clean the end of the metal wire to obtain a pretreated metal wire;
[0022] S2, insert the etched end of the metal wire into the adhesive, remove it, place it in the powder of the metal-organic framework material mentioned above, and cure it to obtain the extraction layer;
[0023] S3. Assemble the metal protective syringe to obtain a solid-phase microextraction probe.
[0024] In this invention, the surface roughness of the metal wire is first improved by chemical etching to increase its loading capacity for metal-organic framework materials. Simultaneously, by impregnating the etched ends of the metal wire with an adhesive, the adhesion between the metal-organic framework material prepared with 2,6-naphthalenedicarboxylic acid as a ligand and the adhesive is enhanced, thereby improving the stability and durability of the extraction layer. Furthermore, using the metal-organic framework material prepared in this invention as an adsorbent, its large specific surface area and high adsorption capacity for substances such as aldehydes can achieve the purpose of high affinity, high capacity, and rapid adsorption and enrichment of target substances.
[0025] Preferably, in step S1, aqua regia is used to etch the end of the metal wire, and then deionized water and ethanol are used for cleaning.
[0026] Specifically, the distance between the etched length and the end of the metal wire is not less than 2 cm.
[0027] Preferably, in S2, the adhesive is silicone.
[0028] For example, the adhesive is a high-temperature flame retardant adhesive, silicone, DJ-A3-BG, or SIDUN3.0 fire-retardant sealant.
[0029] It should be noted that, in order to increase the adhesion of metal-organic framework materials to the metal wire, the etched metal wire is placed in the metal-organic framework material powder, gently rotated, and three layers of metal-organic framework material are repeatedly adhered.
[0030] Furthermore, before extraction using a solid-phase microextraction probe, the solid-phase microextraction probe is aged at 250°C in the gas phase inlet until a stable baseline is obtained.
[0031] In a sixth aspect, the present invention also provides the application of the above-mentioned metal-organic framework material in the detection of VOCs content in exhaled breath.
[0032] In a seventh aspect, the present invention also provides the application of solid-phase microextraction probes in detecting VOCs content in exhaled breath.
[0033] The metal-organic framework material provided by this invention has a high affinity for VOCs in exhaled breath. The solid-phase microextraction probe prepared from it has the advantages of strong coating and high adsorption and extraction efficiency. It can be used to enrich characteristic VOCs in exhaled breath, meet the requirements of trace analysis, and is simple to operate without the need for a large amount of organic solvent. It is an efficient, rapid and sensitive method for detecting VOCs in exhaled breath, with broad application prospects. Attached Figure Description
[0034] Figure 1 SEM image of the metal-organic framework material prepared in Example 1;
[0035] Figure 2 The image shows the FT-IR spectrum of the metal-organic framework material prepared in Example 1.
[0036] Figure 3 The image shows the XRD pattern of the metal-organic framework material prepared in Example 1.
[0037] Figure 4 Thermogravimetric analysis (TGA) of the metal-organic framework material prepared in Example 1;
[0038] Figure 5 SEM images of the extraction layer prepared from the metal-organic framework material in Example 1 at different magnifications;
[0039] Figure 6 SEM image of a cross section of the extraction layer prepared from the metal-organic framework material in Example 1;
[0040] Figure 7 The above are gas chromatograms of solid-phase microextraction and direct injection detection in Example 5. Detailed Implementation
[0041] To make the objectives, technical solutions, and advantages of this invention clearer, the invention will be further described in detail below with reference to embodiments. It should be understood that the specific embodiments described herein are merely illustrative and not intended to limit the invention.
[0042] To better illustrate the present invention, further examples are provided below.
[0043] Example 1
[0044] A method for preparing a metal-organic framework material:
[0045] 0.2162 g (1 mmol) of 2,6-naphthalenedicarboxylic acid, 0.2703 g (1 mmol) of FeCl3·6H2O, and 30 mL of N,N-dimethylformamide were mixed and sonicated for 15 min. The mixture was then placed in an autoclave lined with polytetrafluoroethylene and heated at 200 °C for 10 h. After cooling to room temperature, the mixture was centrifuged and washed three times each with N,N-dimethylformamide and methanol. The resulting solid was stirred with methanol overnight and dried to obtain a metal-organic framework material, denoted as [Fe(2,6-NDC)(DMF).] 1.5 ].
[0046] SEM images of the metal-organic framework material prepared in this embodiment are shown below. Figure 1 As shown in the figure, the metal-organic framework material prepared in this embodiment has a uniform and well-crystallized hexagonal microrod structure.
[0047] The FT-IR image of the metal-organic framework material prepared in this embodiment is shown below. Figure 2 As shown in the figure, at 1657cm -1 The characteristic peak is generated by the asymmetric stretching vibration of CO, at 787 cm⁻¹. -1 The characteristic peaks nearby are those produced by the naphthalene ring, at 1417 cm⁻¹. -1 The characteristic peak is generated by the symmetric stretching vibration of the carboxylate group.
[0048] The XRD pattern of the metal-organic framework material prepared in this embodiment is shown below. Figure 3 As shown in the figure, the metal-organic framework material has obvious diffraction peaks at 11.1°, 12.4°, 15.0°, and 17.7°, proving that the trivalent iron ion successfully coordinates with 2,6-naphthalenedicarboxylic acid.
[0049] Thermogravimetric analysis (TGA) of the metal-organic framework material prepared in this embodiment is shown below. Figure 4 As shown in the figure, the metal-organic framework material exhibits significant weight loss starting from 420℃, indicating that it has good thermal stability and can meet the requirements of gas phase detection.
[0050] Example 2
[0051] A method for preparing a metal-organic framework material:
[0052] 0.1730 g (0.8 mmol) of 2,6-naphthalenedicarboxylic acid, 0.2703 g (1 mmol) of FeCl3·6H2O, and 23 mL of N,N-dimethylformamide were mixed and sonicated for 15 min. The mixture was then placed in an autoclave lined with polytetrafluoroethylene and heated at 180 °C for 15 h. After cooling to room temperature, the mixture was centrifuged and washed three times each with N,N-dimethylformamide and methanol. The resulting solid was stirred with methanol overnight and dried to obtain a metal-organic framework material, denoted as [Fe(2,6-NDC)(DMF).] 1.5 ].
[0053] Example 3
[0054] A method for preparing a metal-organic framework material:
[0055] 0.2595 g (1.2 mmol) of 2,6-naphthalenedicarboxylic acid, 0.2703 g (1 mmol) of FeCl3·6H2O, and 38 mL of N,N-dimethylformamide were mixed and sonicated for 15 min. The mixture was then placed in an autoclave lined with polytetrafluoroethylene and heated at 120 °C for 24 h. After cooling to room temperature, the mixture was centrifuged and washed three times each with N,N-dimethylformamide and methanol. The resulting solid was stirred with methanol overnight and dried to obtain a metal-organic framework material, denoted as [Fe(2,6-NDC)(DMF).] 1.5 ].
[0056] Comparative Example 1
[0057] This comparative example provides a method for synthesizing ZIF-7:
[0058] Under vigorous stirring, 2.0 mL of an aqueous solution of Zn(OAc)2·2H2O (87.8 mg, 0.4 mmol) was added to 2.0 mL of a DMF solution of benzimidazole (CAS: 51-17-2) (94.6 mg, 0.8 mmol). The mixture was stirred at room temperature for 3 min. The resulting emulsion mixture was centrifuged at 10000 r / min for 5 min. The precipitate was washed three times with DMF, water and ethanol in sequence. Finally, it was vacuum dried at 60 °C overnight to obtain a white powdery solid, namely ZIF-7 molecular sieve.
[0059] Comparative Example 2
[0060] This comparative example provides a method for synthesizing MIL-140B(Zr), which specifically includes the following steps:
[0061] 2,6-Naphthalenedicarboxylic acid (1.26 g, 6 mmol), ZrCl4 (0.7 g, 3 mmol), acetic acid (342 μL, 6 mmol) and 15 mL of DMF were mixed and placed in an autoclave. The mixture was heated at 200 °C for 7 h, cooled to room temperature, centrifuged, and washed three times each with DMF and methanol solutions. The solid material was then stirred with methanol overnight and dried to obtain the product, MIL-140B(Zr).
[0062] Comparative Example 3
[0063] This comparative example provides a method for synthesizing MIL-88B(Fe), which specifically includes the following steps:
[0064] 2.7 g (10 mmol) of FeCl3·6H2O and 1.16 g (10 mmol) of H2BDC were mixed into 50 mL of DMF and 4 mL of NaOH2M, and then subjected to sonication for 30 min and magnetic stirring for 30 min. The solution was then transferred to a polytetrafluoroethylene reactor and reacted at 100 °C for 12 h. After cooling to room temperature, the orange solid was collected by centrifugation at 8000 rpm for 5 min. The solid was then suspended in deionized water overnight with stirring for activation. Finally, the product was centrifuged and washed with deionized water and anhydrous ethanol, and then dried at 75 °C for 8 h to obtain MIL-88B(Fe).
[0065] Comparative Example 4
[0066] This comparative example provides a method for synthesizing MIL-100(Fe), which specifically includes the following steps:
[0067] 2.703 g of FeCl3·6H2O and 1.4 g of H3BTC were dissolved in 30 mL of deionized water, and 416 μL of concentrated nitric acid was added. The mixture was stirred for 30 min until completely dissolved. The solution was then transferred to a polytetrafluoroethylene reactor and reacted at 150 °C for 12 h. After cooling to room temperature, the mixture was filtered to obtain a light orange solid product, namely crude MIL-100(Fe).
[0068] The synthesized MIL-100(Fe) was further purified using hot water and ethanol. First, it was boiled in hot water at 80°C for 5 hours to reduce the number of residual unreacted ions, and then boiled in hot ethanol at 60°C for 3 hours until no colored impurities were detected in the mother liquor solution. The solid was then dried at 100°C overnight to obtain the MIL-100(Fe) product.
[0069] Example 4
[0070] A method for preparing a solid-phase microextraction probe, using a stainless steel wire with a diameter of 0.3 mm, specifically includes the following steps:
[0071] S1. The end 2cm of the stainless steel wire was etched with aqua regia (HCl / HNO3 = 3:1, v / v), ultrasonically cleaned with deionized water and anhydrous ethanol for 5 minutes respectively, and air-dried to obtain the pretreated metal wire.
[0072] S2, insert the etched end of the metal wire into the high-temperature flame-retardant adhesive, and slowly remove it. Wipe away the excess adhesive with filter paper, place it in the powder of the metal-organic framework material prepared in Example 1, and gently rotate it. Repeat the adhesion of three layers of the metal-organic framework material prepared in Example 1, and cure in air for 24 hours to obtain the extraction layer.
[0073] S3, Assemble the metal protective syringe to obtain a solid-phase microextraction probe;
[0074] S4. Before conducting the extraction test, the fiber is aged at 250°C in the gas phase inlet until a stable baseline is obtained.
[0075] Solid-phase microextraction probes were prepared from the metal-organic framework materials prepared in Examples 2-3 according to the above method. Solid-phase microextraction probes were also prepared from the materials prepared in Comparative Examples 1-4 according to the above method.
[0076] SEM image of the extraction layer prepared in Example 1 is shown below. Figure 5 As shown in the figure, the fiber coating texture of the extraction layer is clear, meeting the requirements for solid-phase microextraction fibers. The SEM image of the cross-section of the extraction layer is shown below. Figure 6 As shown in the figure, the thickness of the extraction layer is about 30 μm and it is uniformly attached to the fiber surface.
[0077] Example 5
[0078] Performance test for VOCs in exhaled breath:
[0079] 5.1 Solution preparation:
[0080] Add 2.5 μL hexanal, 2.4 μL heptanal, 2.5 μL octanal, 2.4 μL nonanal and 2.4 μL decanal to a 100 mL volumetric flask, dilute to volume with methanol, and shake well to obtain a mixed solution with a concentration of 20 mg / L for each substance.
[0081] The above mixed solution was diluted 10 times with methanol to obtain a mixed standard solution of 2000 μg / mL.
[0082] The above mixed standard solution was serially diluted to mixed solutions of 5 μg / mL, 10 μg / mL, 50 μg / mL, 500 μg / mL, and 1000 μg / mL to obtain linear solutions.
[0083] A 5 μg / mL solution from the linear solution was injected for detection. The limit of detection was 3 × C0 / σ, and the limit of quantitation was 10 × C0 / σ, where C0 is 5 μg / mL and σ is the signal-to-noise ratio.
[0084] Inject 10 μL of the above mixed standard solution into a 30 mL extraction vial. Insert a stainless steel wire containing the extraction layer into the top of the extraction vial for headspace extraction enrichment at 60 °C for 10 min. After extraction, insert the stainless steel wire into the gas chromatograph injection port and desorb at 240 °C for 4 min. Inject and detect the sample under the following chromatographic conditions, and use the above mixed standard solution directly as a control, with an injection volume of 1 μL.
[0085] All analyses were performed using a Trace 1300 gas chromatograph coupled with an ISQ LT mass spectrometer (GC-MS) (Thermo, USA). The chromatographic column was a TG-624 (60 m length, 0.25 mm inner diameter, 1.4 μm film thickness), and high-purity helium (99.999%) was used as the carrier gas at a flow rate of 1 mL / min. -1 The transfer line and ion source were set to 250°C, with a programmed temperature ramp: hold at 80°C for 1 min; then increase at 20°C / min. -1 The temperature was increased to 160°C and held for 1 minute at a heating rate of 10°C / min. -1 Heat to 190℃ and hold for 2 minutes; 5℃·min -1 Raise to 210℃ and hold for 1 minute. Results are as follows: Figure 7 As shown.
[0086] As can be seen from the figure, solid-phase microextraction can effectively improve the detection sensitivity of aldehydes.
[0087] Linear solutions and mixed standard solutions were subjected to solid-phase microextraction under the gas chromatography conditions described above, and the results are shown in Table 1.
[0088] Table 1
[0089]
[0090]
[0091] Based on the gas chromatogram of the above mixed standard solution, the enrichment factor was calculated according to the following formula, and the results are shown in Table 2.
[0092] Enrichment factor EFs = Q SPME / Q in =A SPME / A 直接进样 ×Dilution factor
[0093] Among them, A SPME A represents the peak area in solid-phase microextraction gas chromatography.直接进样 The peak area of the gas chromatogram is obtained by directly injecting the solution; the dilution factor is 300.
[0094] Table 2
[0095]
[0096] In summary, the metal-organic framework material prepared in the embodiments of the present invention can effectively adsorb and enrich VOCs in exhaled breath with high selectivity and high enrichment efficiency. When prepared into a solid-phase microextraction probe, it can effectively detect trace VOCs in exhaled breath without the need for solvents, with fast extraction speed, good reproducibility, and simple operation. It is suitable for a variety of detection instruments and has high potential application value.
[0097] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions or improvements made within the spirit and principles of the present invention should be included within the protection scope of the present invention.
Claims
1. The application of a metal-organic framework material in the detection of trace aldehyde content in exhaled breath, characterized in that, The molecular formula of the metal-organic framework material is: [Fe(2,6-NDC)(DMF)] x ], where 2,6-NDC is 2,6-naphthalenedicarboxylic acid, DMF is N,N-dimethylformamide, Fe is ferric ion, and x=1.
5.
2. A method for preparing the metal-organic framework material according to claim 1, characterized in that, Its preparation method includes the following steps: Soluble ferric salt, 2,6-naphthalenedicarboxylic acid, and N,N-dimethylformamide were mixed evenly, heated, and reacted in a hydrothermal reactor. After solid-liquid separation, washing, and drying, a metal-organic framework material was obtained.
3. The method for preparing the metal-organic framework material as described in claim 2, characterized in that, The soluble ferric salt is ferric chloride; and / or The reaction temperature is 120℃~200℃, and the reaction time is 10h~24h.
4. The method for preparing the metal-organic framework material as described in claim 2 or 3, characterized in that, The molar ratio of the soluble ferric salt to 2,6-naphthalenedicarboxylic acid is 0.8~1.2:1; and / or The molar ratio of N,N-dimethylformamide to soluble ferric salt is 360~410:
1.
5. The application of the metal-organic framework material as an adsorbent in a solid-phase microextraction probe as described in claim 1.
6. A solid-phase microextraction probe, characterized in that, It includes a metal wire, an extraction layer, and a metal protective syringe for protecting the extraction layer; wherein the material of the extraction layer includes the metal-organic framework material as described in claim 1.
7. A method for preparing the solid-phase microextraction probe according to claim 6, characterized in that, Includes the following steps: S1, etch and clean the end of the metal wire to obtain a pretreated metal wire; S2, insert the etched end of the metal wire into the adhesive, remove it, place it in the powder of the metal-organic framework material as described in claim 1, and cure it to obtain the extraction layer; S3. Assemble the metal protective syringe to obtain a solid-phase microextraction probe.
8. The method for preparing the solid-phase microextraction probe as described in claim 7, characterized in that, In S1, aqua regia is used to etch the end of the metal wire, followed by cleaning with deionized water and ethanol; and / or In S2, the adhesive is silicone.
9. The application of the solid-phase microextraction probe according to claim 6 in detecting trace aldehyde content in exhaled breath.
Citation Information
Patent Citations
MIL-53 needle tube-type solid phase microextraction probe and preparation method thereof
CN104043397A
Porous Organic-Inorganic Hybrid Materials with Crystallinity and Method for Preparing Thereof
US20110118490A1